A Case for Critical Realism in Quest of Interdisciplinarity in Research with International Students - Lou, Yingling (Journal of International Students, 2022)
In response to a lack of theoretical engagement and interdisciplinarity in research with international students, this paper explores the affordances of critical realism and the critical realist theory of interdisciplinarity to the field. In so doing, I purport to offer the field an alternative philosophical paradigm and a theoretical blueprint that enables metatheoretical unity and theoretical pluralism to engage interdisciplinarity.